2021
DOI: 10.1007/978-3-030-71119-1_38
|View full text |Cite|
|
Sign up to set email alerts
|

Student Next Assignment Submission Prediction Using a Machine Learning Approach

Abstract: The web-based learning platform provides quality education nowadays, but assignment submission is a critical issue in the e-learning system. Therefore, to investigate assignment submission of the student in advance before the end of course is an important problem. The assignment submission prediction is the advantage of the e-learning system because it allows the instructor to find students' problems on time. Additionally, online learning mostly depends on demographic characteristics such as region, age, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Another more comprehensive study by Y.K. Salal, M. Hussain, and T. Paraskevi focuses on using machine learning techniques including Support Vector Machines (SVM), Random Forest (RF), and Naive Bayes (NB) to predict the next assignment submission of a student and managed to achieve an accuracy of 85.5% [13]. Although the study was conducted dataset of relatively small size, the results implicate its effective extension to larger datasets as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another more comprehensive study by Y.K. Salal, M. Hussain, and T. Paraskevi focuses on using machine learning techniques including Support Vector Machines (SVM), Random Forest (RF), and Naive Bayes (NB) to predict the next assignment submission of a student and managed to achieve an accuracy of 85.5% [13]. Although the study was conducted dataset of relatively small size, the results implicate its effective extension to larger datasets as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While primarily used for binary classification, logistic regression can be extended to handle multinomial outcomes (multiple categories) through variations like multinomial logistic regression. Logistic regression models are widely used in various fields, such as biology and social sciences, where the objective is to predict a categorical outcome [29].…”
Section: B Logistic Regression Classifiermentioning
confidence: 99%
“…In [32][33][34][35], real datasets were used to identify students at risk of failure at an early stage of a semester. In [32], the authors built a model using a deep dense neural network and some traditional ML techniques such as decision tree, Knearest neighbor, random forest, and naïve Bayes, and it showed that AUC and F1-score metrics are better than accuracy in the case of the imbalanced dataset.…”
Section: Related Workmentioning
confidence: 99%
“…The results achieved using all parameters were better than those obtained using only academic parameters. In [35], the authors built a model to predict students' performance in the next assignment submission based on various features such as final result, number of previous attempts, student credit, total clicks, student ID, age, and gender. Random forest, logistic regression, and Knearest neighbor were applied in this study.…”
Section: Related Workmentioning
confidence: 99%